Integrasi Pembelajaran Coding di Sekolah Dasar: Analisis Literatur Terhadap Peran dan Kesiapan Guru di Era Digital - Ahmad Rifa’i; Abdan Rahim; Haji Hamli (PT. Global Pustaka Ilmiah, 2025)
This study aims to analyze the role and readiness of elementary school teachers in implementing coding instruction at the school level. The research employs a literature study (library research) method by reviewing various sources such as scientific journals, books, and relevant documents. The findings indicate that teachers play a highly strategic role in determining the success of coding integration within the school environment. Teachers act as facilitators, instructional designers, and agents of change who bridge digital policies with classroom practices. However, most of the literature reveals that teachers’ readiness remains limited, particularly in the aspects of technopedagogical competence and the use of educational technology. Nevertheless, teachers demonstrate a strong motivation to adapt through training and self-directed learning. This study emphasizes the importance of strengthening teachers’ competencies, improving digital infrastructure, and ensuring continuous policy support so that the implementation of coding instruction in elementary schools can be effective, innovative, and sustainable.